(untitled) (Waretown, NJ., 2014)
This book examines conserved pathways mediating cell cycle progression and cell polarity establishment. It includes examples of yeast, regulatory circuits, and feedback regulation, with emphasis on system-wide approaches. It also covers protein interaction networks and trait locus analysis and presents methods and challenges in comparative genomics analysis and evolutionary genetics.
Keywords: Molecular biology,Yeast fungi,Sinh học phân tử; Molecular genetics